Hak Perempuan dalam Amar Putusan Cerai Menurut Perspektif Maqashid Syari’ah pada Pengadilan Agama Kuala Tungkal Kelas 1B - Heryani; M. Hasbi Umar; Bahrul Ulum (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
This study discusses women’s rights in divorce decisions at the Kuala Tungkal Class 1B Religious Court based on the perspective of Maqashid Syari’ah. Women’s rights decided in divorce, such as iddah maintenance, mut’ah, child custody, and property division, are analyzed in terms of their suitability with the main objectives of Islamic law, namely protection of religion, soul, descendants, mind, and property (Maqashid Syari’ah). This research uses qualitative methods with the normative legal approach. to examine court decisions and how the laws applied reflect the principles of Maqashid Syari’ah. The results of the study indicate that divorce decisions at the Religious Court have considered women’s rights proportionally, although there is still room for further adjustment to be more in line with the essence of Maqashid Syari’ah, especially in terms of economic protection and gender justice. This study recommends the need to strengthen the integration between positive law and sharia principles to better guarantee women’s welfare after divorce.